Perceived benefits as a factor influencing small and medium-sized enterprises (SMEs) in the adoption of digital marketing in Tacloban City, Leyte - Camasin, Ma. Ashley Estudillo; Gamez, Shania Belle H.; Salas, Ruchie M.
The study aims to determine the extent of influence of perceived benefits in the adoption of digital marketing by SMEs in Tacloban City, Leyte, Specifically, it intends to identify the benefits of digital marketing that are perceived by SMEs, to determine how the identified perceived benefits influence the adoption of digital marketing, and to determine the significant relationship between the demographic characteristics and the outcome. This study utilized a quantitative research design. It was conducted within Tacloban City, Leyte, with the respondents being small and medium-sized businesses that were chosen using the simple random sampling technique. A self-made questionnaire consisting of twenty-two (22) questions based on related literature were used. Descriptive statistics as well as eta coefficient and p-value were used for data analysis. The findings suggest that customer engagement and satisfaction is what businesses most consider as a benefit of digital marketing. The findings also reveal that all the perceived benefits can influence the adoption of digital marketing to a great extent. The marketing channels used and the extent of influence of the perceived benefits of digital marketing have a significant relationship. Based on the results, all identified benefits of digital marketing are perceived as benefits by SMEs and these benefits can influence the SMEs' adoption of digital marketing to a great extent. Since there is a significant relationship between the extent of influence of the perceived benefits and the marketing channels used, future studies can further research the connection.